Self-peer Assessment Method in Writing English Teaching Module Based on Merdeka Curriculum - Diani Nurhajati; Yunik Susanti; Dewi Kencanawati; Rika Riwayatiningsih; Firda Anisa Sukmayani; Nike Aprilia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2023)
The research aims to describe the implementation of self-peer assessment method when they were used to improve the English teachers’ ability in writing Phase D English teaching module in Merdeka Curriculum and to know the teachers’ perspective toward its strengths and weaknesses. Twenty-eight Junior High School English teachers in Kediri were the subjects of this study. The data were collected using questionnaire, interview, observation, and documentation. The qualitative data were analysed using qualitative data analysis that consists of three steps; data display, data reduction, and conclusion drawing. While the data got from questionnaire were analysed using statistic descriptive analysis with percentage computation. The results of data analysis showed the steps of implementing Self-Peer Assessment in improving the teachers’ ability in writing English teaching module namely; developing English teaching modules independently after receiving the materials about teaching module; carrying out self-assessment; carrying out peer-assessments; and revising the teaching modules based on assessments and suggestions based on their own and their peers’ comments. The teachers had positive